2020
DOI: 10.3390/jcm9061805
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Pancreatic T1 Values Using Modified Look-Locker Inversion Recovery Sequence (MOLLI) with Pancreatic Exocrine and Endocrine Function

Abstract: Quantifying myocardial T1 values has been useful for detecting and characterizing fibrotic appearance in myocardial infarction, focal scars, and non-ischemic cardiomyopathies. Since pancreatic exocrine function decreases with chronic pancreatic fibrosis advancement, this study examined the correlation between pancreatic T1 values and pancreatic exocrine and endocrine insufficiency. Methods: Thirty-two patients underwent abdominal contrast-enhanced MRI in our department between October 2017 and February 2019. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…T1 mapping has been also tested for the exocrine and endocrine evaluation of pancreatic function. A significant negative correlation was observed between the parenchymal T1 and pancreatic exocrine function measured by fecal elastase-1 dosage, suggesting the possibility of estimating pancreatic exocrine status by pancreatic T1 mapping [28] . Moreover, pancreatic T1 is reported to be significantly longer in type-2 diabetes mellitus than in no-diabetes and prediabetes subjects, and significantly longer in prediabetes than in no-diabetes subjects [29] .…”
Section: T1-mapping and Ecv Quantificationmentioning
confidence: 91%
“…T1 mapping has been also tested for the exocrine and endocrine evaluation of pancreatic function. A significant negative correlation was observed between the parenchymal T1 and pancreatic exocrine function measured by fecal elastase-1 dosage, suggesting the possibility of estimating pancreatic exocrine status by pancreatic T1 mapping [28] . Moreover, pancreatic T1 is reported to be significantly longer in type-2 diabetes mellitus than in no-diabetes and prediabetes subjects, and significantly longer in prediabetes than in no-diabetes subjects [29] .…”
Section: T1-mapping and Ecv Quantificationmentioning
confidence: 91%
“…4,12 Quantitative evaluations of T1 relaxation time can be used at different stages for diagnosing chronic pancreatitis. 6,[13][14][15][16] Type 2 diabetes mellitus (DM2), the most prevalent form of diabetes mellitus, 17 is associated with pancreatic fibrosis secondary to impaired islet cell function. 18 Early diagnosis and treatment of DM2 can reduce the risk of microvascular complications and the mortality rate.…”
Section: Relaxation Timesmentioning
confidence: 99%
“…Recent studies have revealed a positive correlation between the histologic grade of pancreatic fibrosis and T1 relaxation time 4,12 . Quantitative evaluations of T1 relaxation time can be used at different stages for diagnosing chronic pancreatitis 6,13–16 …”
Section: Relaxation Timesmentioning
confidence: 99%
“…Iron-corrected T1 (cT1) is a marker of fibroinflammatory change in MASLD guidelines and guidance ( 7 , 21 , 22 ); cT1 has sensitivity to fat but correlates with liver disease activity from pathology ( 18 , 19 ) and has been shown to predict liver-related outcomes in metabolic dysfunction–associated steatohepatitis (MASH) ( 23 ) and CVD outcomes ( 24 ). In the pancreas, increased T1 relaxation time discriminates acute pancreatitis, resolving in response to anti-inflammatory treatment ( 25 ), can stage chronic pancreatitis ( 26 ) and pancreatic fibrosis ( 27 ), and correlates with reduced exocrine function in pancreatic ductal adenocarcinoma and chronic or autoimmune pancreatitis ( 28 ). In the kidneys, increased T1 correlates with a reduction in renal function (by estimated glomerular filtration rate [eGFR]) ( 29 ), is diagnostic of CKD ( 30 ), and is elevated in the cortex relative to the medulla in kidneys with interstitial fibrosis ( 31 ).…”
Section: Introductionmentioning
confidence: 99%